Preparation of porous polymers by emulsion template method and their use in biodiesel production - Tuncer Ay, Büşra (Graduate School, 2024)
High Internal Phase Emulsions were prepared to obtain highly porous polymers as solid catalysts for esterification of oleic acid with methanol. High internal phase emulsion method enables preparing porous polymers with interconnectivity. However, the surface area of these polymers is extremely constrained as a result of very large pores. This drawback was overcome through hypercrosslinking reaction. PolyHIPEs were prepared using VBC as a monomer and DVB as a crosslinker, followed by a hypercrosslinking process to produce high-surface-area polymers. The hypercrosslinking reaction was applied through Friedel-Crafts alkylation reaction catalyzed by a Lewis acid FeCl3 where chloromethyl group acts as an internal electrophile, and DCE as solvent and external crosslinker. Because DCE has a boiling point of 80°C, it enables the reaction to take place at high temperatures while simultaneously acting as an external crosslinker for the hypercrosslinking process. This reaction produces micro/meso pores and high specific surface area within the framework of polyHIPE precursor. The hypercrosslinking reaction is a controlled reaction that allows an increase of the surface area in a controlled way leaving some unreacted pendant groups. The unreacted pendant groups were employed for additional functionalization on the polymer surface, resulting in acid groups. The catalytic acitivity of the functional unhypercrosslinked and hypercrosslinked solid catalysts were validated through the esterification of oleic acid with methanol for biodiesel production. In addition, this study showed that it is possible to control the amount of sulfonic acid groups and the hydrophobicity of the polymer surface by attaching the sulfonic acid groups in PolyHIPE to the polymer via a methylene bridge. The morpholgy of the polymer surfaces were charactrized by SEM and BET surface area measurements were used to determine the surface area, pore size, and pore size distributions. The surface functionality was characterized by FT-IR and acid-base titration. The good yields were obtained for the esterification reaction with 10% of the solid catalyst at 90oC. Furthermore, the application of the hypercrosslinked solid acid catalyst resulted in enhanced reaction kinetics when compared to the unhypercrosslinked equivalent. The high-surface-area solid acid catalysts can be reused at least four times with relatively negligible activity loss.
Emülsiyon şablon yöntemiyle gözenekli polimerlerin hazırlanması ve biyodizel üretiminde kullanılmaları
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: polymers; polimerler; biodiesel production; biodizel üretimi; fuels; yakıtlar